Cover Image. (29th October 2018) - Pongpipatpaiboon, Kannit; Inamoto, Yoko; Saitoh, Eiichi; Kagaya, Hitoshi; Shibata, Seiko; Aoyagi, Yoichiro; Fujii, Naoko; Palmer, Jeffrey B.; Fernández, Marlís G.
Abstract : The cover image, by Kannit Pongpipatpaiboon et al., is based on the original Article Pharyngeal swallowing in older adults: Kinematic analysis using three‐dimensional dynamic computed tomography . DOI:10.1111/joor.12703 .